Blasingame decline theory for hydrogen storage capacity estimation in shale gas reservoirs. (26th April 2023) - Wei, Mingqiang; Wei, Shihao; Duan, Yonggang; Wang, Hao
Abstract: The estimation of storage capacity is crucial for underground hydrogen storage. Shale gas reservoirs have low permeability and porosity, so it is the potential site for hydrogen storage. The study is based on the depleted shale gas reservoirs with multiple flow mechanisms (diffusion, desorption and seepage). Firstly, this paper, using Laplace transformation, point source function and Stehfest inversion, presents a semi-analytical solution for bottom-hole pressure response with hydrogen duration injection. Then we, considering the multiple flow mechanisms, deduce a material balance equation specifically for shale gas reservoirs and plot modified type curves based on the Blasingame decline analysis theory. Furthermore, we discuss the effects of different critical parameters related to hydrogen storage capacity on type curves. In the final part, we describe in detail the method of obtaining hydrogen reserves using type curves. The proposed one can estimate the hydrogen volume in fractures and matrix systems, and get the actual underground storage volume through pressure response, compared with the hydrogen storage capacity calculated by the volumetric method. This study is helpful for the hydrogen capacity estimation of shale gas underground storage on-site. Highlights: Theoretical derivation addresses the bottom-hole pressure during the hydrogen injection for shale reservoirs. Building the modified Blasingame type curves estimates the hydrogen storage capacity. Fractures' parameters and adsorption index affect the capacity estimation result and reflect in typical curves.